Role of microbes as cleaning degrading industrial wastes for environmental sustainability- A Reveiw. - Sharma, Akash; Mishra, Mohit; Sheet, Simanta; Thite, Mukesh (Recent Research in Science and Technology, 2013)
Public Concern about environment is a very important component necessary for the existence of both man and other biotic organisms. The degree of sustainability of the physical environment is an index of the survival and well-being of the entire components in it. Additionally, it is not sufficient to try disposing toxic/deleterious substances with any known method. The best method of sustaining the environment is such that returns back all the components (wastes) in a recyclable way so that the waste becomes useful and helps the biotic and a biotic relationship to maintain an aesthetic and healthy equilibrium that characterizes an ideal environment. In this review paper we discuss biological method of environmental sustainability which seeks to investigate the various biotechnological tools (biotools) in current use and those undergoing investigations for future use. <!–EndFragment–> <!–ï¿½ï¿½ –>